The Statesman's yearbook 2016 the politics, cultures and economies of the world - Truner, Barry (Palgrave Macmillan, 2015)
Now in its 152nd edition, The Statesman's Yearbook continues to be the reference work of choice for accurate and reliable information on every country in the world. Covering political, economic, social and cultural aspects, the Yearbook is also available online for subscribing institutions: www.statesmansyearbook.com.